Caracterización de los materiales de subrasante en zonas no urbanizadas de la ciudad de Loja, aplicadas a obras de infraestructura vial en el polígono denominado “Carigán” - Tirado Jaya, Carlos Alberto (2015)
Through this project, we will study and characterization of subgrade materials in non-urbanized areas of the city of Loja, applied to road infrastructure will be discussed. The characterization consisted of sampling and testing of selected samples of the study area to obtain parameters for classifying land within groups defined by AASHTO. These tests were conducted in laboratory soil School of Civil Engineering of the Universidad Técnica Particular de Loja. In addition the study of material from a Quarry purposes of improving the quality of the subgrade by the mixing process was performed. To conclude, two maps classification, one according to the classification of the sample, and another with the results of bearing capacity were developed